CHARACTERIZING GEOLOGICAL FACIES USING SEISMIC WAVEFORM CLASSIFICATION IN SARAWAK AND MALAY BASIN OF MALAYSIA - AHMAD ZAILANI, AFIQAH ZAHRAA (2018)
For the past few years, the exploration of oil and gas has become challenging as most of the ‘easy’ hydrocarbon traps are discovered and developed. The remaining hydrocarbon accumulations are now depending mainly on stratigraphic trap or combination of stratigraphic and structural trap which are both difficult to be noticed in seismic sections by using only the interpreter’s eyes. The subtle changes in seismic waveform may indicate the presence of meaningful geological feature or hydrocarbon accumulation which may contains possibility to be developed in future. As the changes in seismic waveform are difficult to be recognized, the automated method with additional machine approach such as neural network will help to classify the waveform to multiple seismic facies classes and delineate the discriminant factor between the classes. The discriminant factors indicate the changes between the seismic waveforms that contribute to identification of geological features and prospects. It is important to identify the geological feature as it can be used to understand the geological facies or depositional environment of the study area. Reservoir efficiency and recovery in terms of porosity and permeability is usually defined based on correctly interpreted depositional environment.